2021
DOI: 10.1002/ca.23801
|View full text |Cite
|
Sign up to set email alerts
|

The effect of respiration and body position on terminal thoracic duct diameter and the lymphovenous junction: An exploratory ultrasound study

Abstract: The thoracic duct (TD) drains most of the body's lymph back to the venous system via its lymphovenous junction (LVJ), playing a pivotal role in fluid homeostasis, fat absorption and the systemic immune response. The respiratory cycle is thought to assist with lymph flow, but the precise mechanism underpinning terminal TD lymph flow into the central veins is not well understood. The aim of this study was to use ultrasonography (US) to explore the relationship between terminal TD lymph flow, the respiratory cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…We did not notice significant differences between men and women. It has been also reported that the TD diameter is dependent on the respiratory phase, as well as it can dilate in diseases causing increased central venous pressure like congestive heart failure or liver cirrhosis with portal hypertension (Hinton et al, 2021; Seeger et al, 2009). This has been also confirmed in chylothorax (Yu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not notice significant differences between men and women. It has been also reported that the TD diameter is dependent on the respiratory phase, as well as it can dilate in diseases causing increased central venous pressure like congestive heart failure or liver cirrhosis with portal hypertension (Hinton et al, 2021; Seeger et al, 2009). This has been also confirmed in chylothorax (Yu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…T A B L E 1 Summary of TD anatomy and physiology findings Sonography studies provide different perspective for the TD anatomy assessment (Hinton et al, 2021;Seeger et al, 2009). Ultrasound allowed to visualize the TD in majority of patients or healthy volunteers.…”
Section: Anatomymentioning
confidence: 99%
See 1 more Smart Citation